PROFIL KARAKTERISTIK KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) VAKSIN CORONA VIRUS JENIS SINOVAC PADA PERAWAT KLINISI : CROSS-SECTIONAL STUDY: PROFIL KARAKTERISTIK KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) VAKSIN CORONA VIRUS JENIS SINOVAC PADA PERAWAT KLINISI : CROSS-SECTIONAL STUDY - widiyono, widiyono; Praspaskalis Anes, G. Yosse (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2024)
Background: Nurses have an important role in treating patients affected by the corona virus. One of the efforts to prevent transmission is the provision of vaccination. Reactions that appear after vaccination is a natural thing. AEFI or Post-Immunization Adverse Events are generally temporary. Objective: To describe the characteristics of adverse events after immunization with the moderna type of covid-19 vaccine for nurses at the Santo Vincentius Hospital, Singkawang, West Kalimantan. Methods: This research uses quantitative descriptive with cross-sectional method. This research was conducted online through the google-form application by nurse respondents in their respective work areas. Data collection using purposive sampling technique with the number of respondents as many as 50 nurses. Results: The study found that 80% of nurses who received the Sinovac vaccine experienced AEFI. The symptoms that appear are dominated by soreness in the left arm of the injection site as much as 80% and fever as much as 70%. Conclusion: The characteristics of the emergence of AEFI in nurses who received the Sinovac type of Corona virus vaccination in this study were based on age, gender, disease history, number of AEFI incidents, types of AEFI symptoms, and duration of AEFI symptoms that appeared. Nurses already have knowledge in dealing with emerging AEFIs.